Effectiveness of an Online Body Camera System for Medical Oversight in Prehospital Emergency Care: An 11-Year Retrospective Cohort Study - Phontabtim, Malivan; Yuksen, Chaiyaporn; Trakulsrichai, Satariya; Sricharoen, Pungkava; Aramvanich, Kasamon; Tienpratarn, Welawat; Damdin, Siriporn; Seesuklom, Suteenun; Thiamdao, Natthaphong; Palee, Chantarat; et al. (Archives of Academic Emergency Medicine, 2026)
Introduction: The online body camera system (OBCS) integrates telemedicine technology with real-time monitoring of on-scene operations, direct online medical direction, and coordinated patient care. This study aimed to evaluate its effectiveness compared with the traditional telephone-based medical oversight system. Methods: This retrospective cohort study evaluated the effectiveness of OBCS in prehospital emergency care of Ramathibodi Hospital by comparing outcomes (survival rate, length of stay) between the traditional telephone-based (2014–2021) and the OBCS periods (2022–2024) in emergency medical operation unit. Results: This 11-year retrospective cohort study analyzed 5,721 prehospital emergency care cases (3,398 cases managed under the traditional telephone-based system and 2,323 cases managed under the OBCS). The findings indicate that the implementation of the OBCS significantly improved overall survival to emergency department (ED) arrival (adjusted odds ratio (aOR) = 8.32, 95% CI: 1.47–47.14, P = 0.017), particularly among out-of-hospital cardiac arrest (OHCA) patients (aOR = 7.99, 95% CI: 1.28–50.03, P = 0.026). However, the new system did not result in significant improvements in survival to hospital admission or survival to hospital discharge. Furthermore, the length of stay (LOS) in the ED, intensive care unit (ICU), and overall hospital setting remained unchanged. Conclusions: The OBCS significantly enhanced survival to ED arrival, particularly among OHCA patients. However, the LOS in the ED, ICU, and overall hospital setting remained unchanged.